Regulation of synaptic acetylcholine concentrations by acetylcholine transport in rat striatal cholinergic transmission. Issue 1 (18th August 2017) - Muramatsu, Ikunobu; Uwada, Junsuke; Masuoka, Takayoshi; Yoshiki, Hatsumi; Sada, Kiyonao; Lee, Kung‐Shing; Nishio, Matomo; Ishibashi, Takaharu; Taniguchi, Takanobu
Abstract: In addition to hydrolysis by acetylcholine esterase (AChE), acetylcholine (ACh) is also directly taken up into brain tissues. In this study, we examined whether the uptake of ACh is involved in the regulation of synaptic ACh concentrations. Superfusion experiments with rat striatal segments pre‐incubated with [ 3 H]choline were performed using an ultra‐mini superfusion vessel, which was developed to minimize superfusate retention within the vessel. Hemicholinium‐3 (HC‐3) at concentrations less than 1 μM, selectively inhibited the uptake of [ 3 H]choline by the high affinity‐choline transporter 1 and had no effect on basal and electrically evoked [ 3 H]efflux in superfusion experiments. In contrast, HC‐3 at higher concentrations, as well as tetraethylammonium (>10 μM), which inhibited the uptake of both [ 3 H]choline and [ 3 H]ACh, increased basal [ 3 H]overflow and potentiated electrically evoked [ 3 H]efflux. These effects of HC‐3 and tetraethylammonium were also observed under conditions where tissue AChE was irreversibly inactivated by diisopropylfluorophosphate. Specifically, the potentiation of evoked [ 3 H]efflux was significantly higher in AChE‐inactivated preparations and was attenuated by atropine. On the other hand, striatal segments pre‐incubated with [ 3 H]ACh failed to increase [ 3 H]overflow in response to electrical stimulation. These results show that synaptic ACh concentrations are significantly regulated by the postsynaptic uptake of ACh, as well as by AChE hydrolysis and modulation of ACh release mediated through presynaptic muscarinic ACh receptors. In addition, these data suggest that the recycling of ACh‐derived choline may be minor in cholinergic terminals. This study reveals a new mechanism of cholinergic transmission in the central nervous system. Abstract : In central cholinergic transmission, synaptic concentration of acetylcholine (ACh) is significantly regulated by postsynaptic uptake of ACh through putative ACh transporter (AChT), hydrolysis of ACh by acetylcholine esterase (AChE) and autoregulation of presynaptic ACh release by presynaptic ACh receptors (AChRs). ACh‐derived choline may not be effectively recycled for ACh synthesis.